A detailed view of the injection‐induced seismicity in a natural gas reservoir in Zigong, southwestern Sichuan Basin, China. Issue 8 (20th August 2013) - Lei, Xinglin; Ma, Shengli; Chen, Wenkang; Pang, Chunmei; Zeng, Jie; Jiang, Bing
Abstract: [1] Seismicity at a gas reservoir located in the relatively stable Sichuan Basin, China, mirrors the injection pressure of unwanted water, suggesting that the seismicity is injection induced. Injection under high pressure on a routine basis began on 9 January 2009 and continued to July 2011. During the injection period, over 120, 000 m 3 of water was pumped under a wellhead pressure of up to 6.2 MPa into the limestone formation of Permian 2.45 to 2.55 km beneath the surface. The injection induced more than 7000 surface‐recorded earthquakes, including 2 M 4+ (the largest one was ML 4.4), 20 M 3+, and more than 100 M 2+ events. Data observed by a nearby local seismic network and five temporal stations provide a detailed view of the spatiotemporal distribution of the induced earthquakes. Most events were limited to depths ranging from 2.5 to 4 km, which is consistent with the limestone formation of Permian. In a map view, hypocenters are concentrated in a NNW extended ellipsoidal zone approximately 6 km long and approximately 2 km wide centered approximately at the injection well. Multisources of evidence such as the shear mechanism, pattern of hypocenter distribution, and small elevated pore pressure as compared with the least principal stress in the region show that the induced earthquakes occurred as a result of lowering of the effective normal stress on known or unknown preexisting blind faults which are critically loaded under the regional stress field. Epidemic‐type aftershock sequence modeling results indicate that injection inducing and earthquake triggering are both important during earlier periods of injection, while later periods are dominated by forced (injection‐induced) seismicity. Key Points: Injection‐induced seismicity of more than 7, 000 earthquakes up to M4.4 Injection‐inducing and earthquake triggering are both important Multi sources of evidence show reactivation of pre‐existing blind faults